Analysis of Trends in the Development of Agricultural Enterprises and the Formation of Operating Profit - Vinnichek Lyubov (EDP Sciences, 2021)
In agricultural business, some specific factors, such as high natural and climatic risks, seasonality of production, reliance on biological assets, slow cycle of capital turnover, timeliness and completeness of budgetary assistance, have a significant impact on financial results. The role of budgetary funds in modern conditions is clearly manifested at the stage of formation and presentation of operating profit in the reports of an agricultural enterprise. The analysis of profit and assessment of its basis of efficiency of business processes of the enterprise are the most important direction of financial analysis of market entities' activity. Information about the amount of operating profit is an economic criterion for the development of an agricultural enterprise and can be a signal reference point for potential investors in the agricultural market when considering business cooperation and partnership.